Kim Kardashian is my new BFF: Video games and the looking glass celebrity. (3rd July 2018) - Chess, Shira; Maddox, Jessica
ABSTRACT: Mobile-based celebrity games are a by-product of a new, more feminized video game industry. Within celebrity games, the player engages with celebrity culture in a variety of ways, often being transformed into their own brand of celebrity. Celebrity games are a form of hypertrophic media, based on the dyadic interactions between the player and celebrity. Within this, one becomes a looking-glass celebrity—an enculturation process by which the celebrity text situates the player as closer to the titular star than the player actually is. In turn, the player uses this position to reflexively construct what the player believes constitutes a successful celebrity. The path to fame, however, is a hollow one, wherein the player can never really lose and never really win.